Portrait of Jason (1967) - Clarke, Shirley ([United Kingdom] : Second Run DVD, 2005)
Portrait of Jason is the raw record of a confessional conversation with an African-American gay hustler recounting his life and times. A disturbing and fascinating document, it unflinchingly observes Jason Holliday - conversing, performing, confessing, dissolving.
English spoken
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Clarke, Shirley